A cucurbit[6]uril-based supramolecular assembly as a highly sensitive and quickly responsive luminescent sensor for the detection of fluoroquinolone antibiotics in simulated wastewater. Issue 22 (27th May 2020) - Shi, Lulu; Liu, Mei; Li, Hui
Abstract : A highly sensitive and quickly responsive CB[6]-based supramolecular assembly was synthesized and used to detect antibiotics through luminescence quenching. Abstract : A unique cucurbit[6]uril-based (CB[6]) supramolecular assembly [Na4 CB[6](H2 O)10 DMF]·2BPDS·2H2 O (1 ) was successfully synthesized by using an aromatic compound 4, 4′-biphenyldisulphonic acid (H2 BPDS) as a structure-directing agent. More impressively, 1 displayed high sensitivity and quick response toward two commonly used fluoroquinolone antibiotics, levofloxacin (LUX) and gatifloxacin (GAT), through luminescence quenching.